2019
DOI: 10.7126/cumudj.554999
|View full text |Cite
|
Sign up to set email alerts
|

Usage of Rotary Instruments in Root Canal Therapy of Deciduous Teeth - Review

Abstract: Maintaining the deciduous teeth in the mouth until the time of physiological exfoliation is of great importance for the health of the permanent dentition. Root canal treatment, also called pulpectomy, performed in cases of inflammation or necrosis of the deciduous teeth pulp, is indicated as a successful method to preserve the tooth functionally. Conventional pulpectomy procedure is performed with stainless steel files, however, the low elasticity of these files may cause undesirable canal shapes and the timet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…It is noteworthy that although we did not observe a significant difference in the duration of treatment when we compared the file preference with the duration of treatment in our study, many recent studies have reported that a pediatric canal file or rotary file facilitates a faster preparation process [ 5 , 41 45 ].…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…It is noteworthy that although we did not observe a significant difference in the duration of treatment when we compared the file preference with the duration of treatment in our study, many recent studies have reported that a pediatric canal file or rotary file facilitates a faster preparation process [ 5 , 41 45 ].…”
Section: Discussioncontrasting
confidence: 72%
“…Root canal treatment of deciduous teeth should be performed within a short period and with minimal complications. Effective shaping and debridement without weakening the tooth structure and damaging the permanent tooth germ is crucial [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, success of the pulp treatment procedure mainly depends upon the speed of disinfection, the provision of optimal asepsis without weakening the walls or affecting the successor tooth germ and the guarantee that the tooth is conserved until its physiological exfoliation [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, rotary Ni-Ti systems have been introduced with a wide range of designs and usage techniques, allowing for faster preparation while preserving the original shape, even of curved root canals [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the increasing number of patients consulting to the pediatric dentistry clinics due to modern advances in dental caries prevention and the preservation of natural dentition; premature loss of primary teeth is still a common problem. [1][2][3][4] This is considered to be the most important cause of dental and skeletally malocclusion. 5,6 In these cases, it is necessary to use of space maintainers in order to keep the existing space in the dental arch and prevent the development of malocclusion by tilting the adjacent and opposite teeth.…”
Section: Introductionmentioning
confidence: 99%